Field notes contributed by Carl J. Bendorf, spring 1987 - Bendorf, Carl J.et al (1987)
List of birds and locations contributed by Carl J. Bendorf with observers Thomas H. Kent and Steve Larson. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of spring 1987. Epson - sheet feed/flatbed